Gramsci, the “Club di vita morale” and the Meditations by Marcus Aurelius - Francese, Joseph (International Gramsci Journal, 2025)
In what follows I analyse elements of stoicism taken by Gramsci from the Meditations di Marcus Aurelius, a text read by Gramsci as a young man, then conveyed to the members of the “Club of Moral Life”, a small study group of young socialists organized in Turin under his direction in 1917-1918. Gramsci uses the Emperor’s memories to teach how and why the individual must comport themselves as ethical and rational members of society and must strive to improve their community through example and teaching. Gramsci also takes from Marcus Aurelius the need to teach the Other to think independently, engage with the new, and attain a democratic view of life, that is, to see the Other as “another myself” who, like the instructor, finds within themself the truth of their life in society and teaches others to do the same. From such a perspective, this goal of self-education (to know oneself better so as to continually become a better person), teach, and act in the political arena (through propaganda and proselytizing) so as to transform ‘molecularly’ the polis are all one and the same.